Bi2S3 / Bi2O2CO3 nanosheet catalyst as well as preparation method and application thereof
By preparing Bi2S3/Bi2O2CO3 nanosheet catalyst, the problems of low Faradaic efficiency and poor stability of existing electrocatalytic carbon dioxide reduction to formic acid catalysts are solved, and efficient and stable electrocatalytic performance of carbon dioxide reduction to formic acid is achieved.
Patent Information
- Application Number
- CN202411467364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
AI Technical Summary
The existing catalysts for electrocatalyzing carbon dioxide reduction formic acid have problems with low Faraday efficiency and poor stability, and bismuth oxygen carbonate-related materials are not suitable for electrocatalysis.
Bi2S3/Bi2O2CO3 nanosheet catalyst is used. The catalyst is prepared by adding the Bi2O2CO3 precursor to a solution containing thioacetamide at room temperature and stirring to form a nanosheet structure. The active center metal element Bi2S3/Bi2O2CO3 interface is randomly distributed.
Under neutral and alkaline conditions, high electrical catalytic restoration of carbon dioxide noric acid has good stability and high selectivity. It is suitable for industrial electrical catalytic carbon dioxide reduction.
Smart Images

Figure CN119332290A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic carbon dioxide reduction to formic acid production, and specifically relates to a Bi2S3 / Bi2O2CO3 nanosheet catalyst and a preparation method and application thereof. Background Art
[0002] Due to the continuous development of industrial civilization, the emission of greenhouse gases has led to the deterioration of the global environment. Carbon dioxide, as the main component of greenhouse gases, can be used as a raw material to be reduced to high-value chemical raw materials through electrocatalysis, which can not only fix carbon dioxide but also achieve energy storage. Electrocatalytic carbon dioxide reduction can produce different products, such as single-carbon products (formic acid, carbon monoxide, methane), multi-carbon products (ethylene, ethane, etc.). Among them, formic acid (salt), as an important chemical raw material, can also be used as an ideal hydrogen carrier and liquid fuel for formic acid (salt) fuel cells. With the construction of new power generation equipment such as solar power generation, wind power generation, and hydropower generation, the electricity generated can be used as a power source for electrocatalytic carbon dioxide reduction to produce formic acid.
[0003] Patent CN114210353A discloses a method for preparing a bismuth carbonate-bismuth sulfide heterostructure photocatalytic material, comprising the following steps: (1) adding urea to deionized water, stirring and dissolving, then adding Bi(NO3)3·5H2O and continuing to stir, and then adding sodium sulfide to obtain a mixed solution; (2) stirring the mixed solution, and then reacting it in a closed manner. After the reaction is completed, it is naturally cooled to room temperature, the product is centrifuged, washed with water, washed with alcohol, and dried at room temperature to obtain a bismuth carbonate-bismuth sulfide heterostructure photocatalytic material. It can effectively solve the problem that bismuth carbonate as a photocatalytic material is insufficiently responsive to ultraviolet light, and compared with other bismuth carbonate-bismuth sulfide heterojunctions, the preparation method is simple, low-cost, and easy to mass produce. The current bismuth carbonate-related materials are mainly used for photocatalysis and are not very suitable for electrocatalysis. In addition, there are currently many competing reactions (hydrogen evolution reaction, reduction of carbon dioxide to carbon monoxide) in the electrocatalytic reduction of carbon dioxide to produce formic acid (salt), which results in the Faraday efficiency of formic acid (salt) failing to maintain a high level, and the poor stability of the catalyst also limits its large-scale application. Summary of the invention
[0004] The invention provides a Bi2S3 / Bi2O2CO3 nanosheet catalyst and a preparation method and application thereof. The catalyst is prepared by adding a synthesized Bi2O2CO3 precursor to a solution containing thioacetamide at room temperature and stirring. The catalyst has a nanosheet structure, and interfaces of active center metal single substance Bi2S3 / Bi2O2CO3 are randomly distributed in the nanosheets. The catalyst exhibits high ability to produce formic acid by electrocatalytic reduction of carbon dioxide under neutral and alkaline conditions and has good stability. The preparation method is simple, inexpensive, easy to control, excellent in performance, easy to mass produce, and suitable for industrial electrocatalytic reduction of carbon dioxide to produce formic acid.
[0005] The technical solution of the present invention is:
[0006] In the first aspect, a Bi2S3 / Bi2O2CO3 nanosheet catalyst is disclosed. The Bi2S3 / Bi2O2CO3 nanosheet is represented by the (011) and (013) crystal planes of Bi2O2CO3 and an amorphous crystalline phase of Bi2S3, and the Bi2S3 / Bi2O2CO3 interface is randomly distributed in the nanosheet.
[0007] In the second aspect, a method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst is disclosed, wherein Bi2O2CO3 nanoflowers are generated by a hydrothermal method, and then added into an aqueous solution containing thioacetamide and stirred to react to generate the Bi2S3 / Bi2O2CO3 nanosheet catalyst.
[0008] Preferably, the method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst comprises the following steps:
[0009] 1) adding the raw material bismuth nitrate pentahydrate to a nitric acid solution containing citric acid monohydrate, stirring the solution evenly, adjusting the pH of the solution, transferring the solution to a hydrothermal kettle for hydrothermal reaction, taking out, centrifuging, washing, and drying to obtain Bi2O2CO3 nanoflowers;
[0010] 2) Add Bi2O2CO3 nanoflowers into an aqueous solution containing thioacetamide and stir to obtain Bi2S3 / Bi2O2CO3 nanosheet catalyst.
[0011] Preferably, in step 1), when the pH of the solution is adjusted to 7-9, especially 8, with an aqueous solution of potassium hydroxide, the morphology of the synthesized series of Bi2O2CO3-based catalysts is more uniform, and the two-dimensional Bi2S3 / Bi2O2CO3 nanosheet catalyst has a better electrocatalytic carbon dioxide reduction activity.
[0012] Preferably, in step 1), the hydrothermal reaction temperature is 160-200° C., preferably 180° C., and the reaction time is 16-28 h, preferably 24 h.
[0013] Preferably, in step 1), the washing is performed with ultrapure water and ethanol respectively.
[0014] Preferably, in step 2), the molar ratio of Bi2O2CO3 nanoflowers to thioacetamide is (1-3):1, and the preferred molar ratio is 1.5:1.
[0015] Preferably, in step 2), the stirring temperature is 20-30° C., and the stirring time is 1-3 h, preferably 2 h.
[0016] In a third aspect, the application of the Bi2S3 / Bi2O2CO3 nanosheet catalyst in the electrocatalytic production of formic acid from carbon dioxide is disclosed, especially in the electrocatalytic reduction of carbon dioxide to formic acid under alkaline conditions and near-neutral conditions.
[0017] The present invention uses cheap and low-toxic bismuth nitrate pentahydrate as a raw material, and prepares Bi2O2CO3 nanoflowers through a simple hydrothermal reaction. The nanoflowers are added into an aqueous solution containing thioacetamide for stirring reaction at room temperature to generate Bi2S3 / Bi2O2CO3 nanosheets. A large number of interfaces between Bi2S3 and Bi2O2CO3 can be formed. The interfaces serve as active sites to significantly enhance the activity of the Bi2S3 / Bi2O2CO3 nanosheet catalyst in electrocatalytic reduction of carbon dioxide to formic acid, thereby obtaining an electrocatalyst with electrocatalytic reduction of carbon dioxide to formic acid activity. Tests show that the product has excellent catalytic activity and catalytic stability.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. Compared with the Bi2O2CO3 nanoflower catalyst, the potential window range of the Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared by the present invention for electrocatalytic carbon dioxide reduction to formic acid (selectivity ≥ 90%) is greatly widened, and the selectivity for formic acid is higher at the same potential, showing that the Bi2S3 / Bi2O2CO3 nanosheet catalyst has good performance in catalyzing carbon dioxide to formic acid.
[0020] 2. The present invention uses hydrophobic carbon paper as a carrier when preparing the working electrode, so that Bi2S3 / Bi2O2CO3 nanosheets grow on its surface, which can further expose a large number of active sites and further enhance the performance of the material;
[0021] 3. The raw materials for material synthesis are widely available and cheap, the synthesis method is simple, and the controllability is strong, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1It is a comparison chart of the XRD patterns of the Bi2O2CO3 nanoflowers prepared in step 1) of Example 1 of the present invention and the Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in step 2) with the standard card of the Bi2O2CO3 nanosheet.
[0023] Figure 2 These are scanning and transmission electron micrographs of the Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in Example 1 of the present invention, where a is a scanning electron micrograph, b is a transmission electron micrograph, and c is a high-resolution transmission electron micrograph.
[0024] Figure 3 : a is a performance diagram of catalytic carbon dioxide to formic acid when electrochemical linear sweep voltammetry test is performed on Bi2S3 / Bi2O2CO3 and Bi2O2CO3 prepared in step 1) of Example 1 in Example 4 of the present invention, b is a performance diagram of catalytic carbon dioxide to formic acid when electrochemical linear sweep voltammetry test is performed in Example 5 of the present invention, c is a Faraday efficiency diagram of catalytic carbon dioxide to formic acid in Example 5 of the present invention, and d is a diagram of the selectivity of Bi2S3 / Bi2O2CO3 nanosheet catalyst and Bi2O2CO3 nanoflower catalyst for formic acid at the same potential in Example 5.
[0025] Figure 4 : a is the Faraday efficiency of the gas products of the Bi2S3 / Bi2O2CO3 nanosheet catalyst at each current density in the flow-type electrolyzer in Example 6; b is the Faraday efficiency of the gas products of the Bi2S3 / Bi2O2CO3 nanosheet catalyst at each current density in the flow-type electrolyzer in Example 7; c is the stability test graph of the catalytic carbon dioxide to formic acid during the electrochemical chronoamperometry test in Example 8 of the present invention. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0027] Example 1
[0028] The preparation of Bi2S3 / Bi2O2CO3 nanosheet catalyst comprises the following steps:
[0029] 1) 7 mL of nitric acid and 1 mmol of monohydrated citric acid were added to 30 mL of ultrapure water in sequence, and after stirring for 5 minutes, the pH of the solution was adjusted to 8 with potassium hydroxide aqueous solution, and 1.5 mmol of bismuth nitrate pentahydrate was added and stirred for 5 minutes; the solution was transferred to a hydrothermal reactor, reacted at 180°C for 24 hours, and after cooling to room temperature, taken out, washed three times each with ultrapure water and ethanol by centrifugation, taken out, and vacuum dried for 12 hours to obtain Bi2O2CO3 nanoflowers, whose XRD pattern is shown as follows Figure 1 As shown;
[0030] 2) 0.25 g Bi2O2CO3 nanoflowers and 0.15 g thioacetamide were dissolved in 80 mL ultrapure water, stirred for 2 h, taken out, washed three times by centrifugation with ultrapure water and ethanol, taken out, and vacuum dried for 12 h to obtain Bi2S3 / Bi2O2CO3 nanosheet catalyst. The XRD characteristics of the catalyst are as follows: Figure 1 The scanning electron microscope image, transmission electron microscope image, and high-resolution transmission electron microscope image of the catalyst are shown in Figure 2 As shown, it is proved that the Bi2S3 component of the material is amorphous hemispherical and evenly distributed on the Bi2O2CO3 surface.
[0031] Example 2
[0032] The preparation of Bi2S3 / Bi2O2CO3 nanosheet catalyst comprises the following steps:
[0033] 1) 7 mL of nitric acid and 1 mmol of monohydrated citric acid were added to 30 mL of ultrapure water in sequence, and after stirring for 5 minutes, the pH of the solution was adjusted to 9 with an aqueous potassium hydroxide solution, and 1.5 mmol of bismuth nitrate pentahydrate was added and stirred for 5 minutes; the solution was transferred to a hydrothermal reactor, reacted at 180° C. for 24 h, and after cooling to room temperature, taken out, washed three times each with ultrapure water and ethanol by centrifugation, taken out, and vacuum dried for 12 h to obtain Bi2O2CO3 nanoflowers;
[0034] 2) Dissolve 0.25 g Bi2O2CO3 nanoflowers and 0.15 g thioacetamide in 80 mL ultrapure water, stir for 2 h, take out, wash three times each with ultrapure water and ethanol by centrifugation, take out, and vacuum dry for 12 h to obtain Bi2S3 / Bi2O2CO3 nanosheet catalyst.
[0035] Example 3
[0036] The preparation of Bi2S3 / Bi2O2CO3 nanosheet catalyst comprises the following steps:
[0037] 1) 7 mL of nitric acid and 1 mmol of monohydrated citric acid were added to 30 mL of ultrapure water in sequence, and after stirring for 5 minutes, the pH of the solution was adjusted to 7 with an aqueous potassium hydroxide solution, and 1.5 mmol of bismuth nitrate pentahydrate was added and stirred for 5 minutes; the solution was transferred to a hydrothermal reactor, reacted at 180° C. for 24 h, and after cooling to room temperature, taken out, washed three times each with ultrapure water and ethanol by centrifugation, taken out, and vacuum dried for 12 h to obtain Bi2O2CO3 nanoflowers;
[0038] 2) Dissolve 0.25 g Bi2O2CO3 nanoflowers and 0.15 g thioacetamide in 80 mL ultrapure water, stir for 2 h, take out, wash three times each with ultrapure water and ethanol by centrifugation, take out, and vacuum dry for 12 h to obtain Bi2S3 / Bi2O2CO3 nanosheet catalyst.
[0039] Example 4
[0040] The Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in Example 1 was used to carry out measurement in an H-type electrolyzer, and a working curve of the catalytic activity of carbon dioxide reduction in a 0.5M KHCO3 solution was drawn:
[0041] a. First, prepare the working electrode: take 5 mg of the Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in Example 1 and disperse it in a mixed solution of 485 μL of water and 485 μL of ethanol, then add 30 μL of Nafion solution, ultrasonicate for 30 minutes to make the solution uniformly dispersed, and drop the solution on the surface of the hydrophobic carbon paper to ensure that the catalyst loading is 1 mg / cm 2 Then, the hydrophobic carbon paper is clamped on the electrode holder so that it is immersed in the 0.5M KHCO3 solution. The size of the material is 1*1cm 2 , this electrode is the working electrode, the platinum sheet is the auxiliary electrode, and Ag / AgCl is the reference electrode;
[0042] b. Use an electrochemical workstation to test with a three-electrode system, and use linear sweep voltammetry to detect material properties. The initial voltage is set to -0.4V, the end voltage is -1.2V, and the scan rate is 10mV / s. Record the working curve. The results are as follows Figure 3 As shown in a.
[0043] The performance of Bi2O2CO3 prepared in step 1) of Example 1 was tested in an H-type electrolytic cell in the same manner as above. The test results are as follows: Figure 3 As shown in a, the Bi2S3 / Bi2O2CO3 nanosheet catalyst obtained after a series of treatments has a higher current density than the Bi2O2CO3 nanoflower catalyst at the same potential.
[0044] Example 5
[0045] The catalyst in Example 1 was used to perform the test in an H-type electrolyzer, and a performance curve of the catalytic activity of carbon dioxide reduction in a 0.5M KHCO3 solution was drawn:
[0046] A. Using an electrochemical workstation to test with a three-electrode system, the working electrode was prepared according to the method of step a) in Example 4, and the portion of the electrode that penetrated into the 0.5M KHCO3 solution was 1*1 cm 2 , platinum sheet was used as auxiliary electrode and Ag / AgCl as reference electrode;
[0047] B. Using the chronoamperometry, the initial voltage is set to -0.65V, the end voltage is -1.25V, and the test is performed every 0.1V for 30 minutes. The working curve is recorded. The results are as follows: Figure 3 As shown in b, during the test, the gas sample enters the gas chromatograph for detection in real time, and the Faraday efficiency of formic acid is calculated as follows: Figure 3 c, the determination formula of gas products is Where V i is the volume concentration of the gas measured by gas chromatography, n is the number of transferred electrons to generate the gas product (2 for H2 and CO), and F is the Faraday constant (96500C mol -1 ), P0 is normal pressure (101325Pa), i is current density, T0 is normal temperature (298.15K). The determination formula of liquid product is Where V is the volume of the cathode electrolyte, C is the concentration of formic acid (determined by NMR), n is the number of electrons transferred to generate formic acid (2), and F is the Faraday constant (96500 Cmol -1 ), Q is the number of charges transferred during the electrolysis process. The test method for formic acid selectivity is: take 500 μl of the tested electrolyte, add 100 μl of deuterated water, and then add 100 μl of DMSO solution, perform nuclear magnetic resonance hydrogen spectrum detection on the solution to obtain the concentration of formate, and the specific calculation formula is Where S is the proportional coefficient of the calculation, which is 731, Q is the number of charges consumed during the electrolysis process, and A HCOO- HCOO in NMR - The peak area, A DMSO is the peak area of DMSO in the NMR spectrum, and the selectivity of formic acid is Figure 3 As shown in d, the Bi2O2CO3 prepared in step 1) of Example 1 was tested in the same manner. The Bi2S3 / Bi2O2CO3 nanosheet catalyst had a higher selectivity for formic acid than the Bi2O2CO3 nanoflower catalyst at the same potential, and the potential window range in which the selectivity for formic acid exceeded 90% was wider.
[0048] Example 6
[0049] The Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in Example 1 was measured in a flow-type electrolyzer to draw a performance curve of the carbon dioxide reduction catalytic activity in a 1M KOH solution:
[0050] ① The electrochemical workstation was used to test the three-electrode system. The working electrode was prepared according to the method in step a) of Example 4, and the portion of the electrode in contact with the 1M KOH solution was 1*1 cm 2 , with platinum as auxiliary electrode and Hg / HgO as reference electrode;
[0051] ② The material properties were tested using the step constant current-time method, with an initial current density of 200 mA / cm 2 , the termination current density is 1000mA / cm 2 During the test, the gas sample enters the gas chromatograph for real-time detection, and the Faraday efficiency of the gas product at each current density is recorded. Figure 4 As shown in a, at 200 mA cm -2 ~1000mA cm -2 The selectivity for formic acid is nearly 100% within the current density range.
[0052] Example 7
[0053] The Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in Example 1 was measured in a flow-type electrolyzer to draw a performance curve of the carbon dioxide reduction catalytic activity in a 0.5M KOH solution:
[0054] ① The three-electrode system was used for testing using an electrochemical workstation. The working electrode was prepared according to the method in step a) of Example 4, and the portion of the electrode in contact with the 0.5 M KOH solution was 1*1 cm 2 , platinum sheet was used as auxiliary electrode and Hg / HgO as reference electrode;
[0055] ② The material properties were tested using the step constant current-time method, with an initial current density of 200 mA / cm 2 , the termination current density is 1000mA / cm 2 During the test, the gas sample enters the gas chromatograph for real-time detection, and the Faraday efficiency of the gas product at each current density is recorded. Figure 4 As shown in b, at 200mAcm -2 ~1000mA cm -2 The selectivity for formic acid is nearly 100% within the current density range.
[0056] Example 8
[0057] The Bi2S3 / Bi2O2CO3 nanosheet catalyst prepared in Example 1 was measured in a flow-type electrolyzer to draw a performance curve of the catalytic stability of carbon dioxide reduction in a 0.5M KHCO3 solution:
[0058] ① The electrochemical workstation was used to test the three-electrode system. The working electrode was prepared according to the method in step a) of Example 4, and the portion of the electrode in contact with the 0.5M KHCO3 solution was 1*1cm 2 , platinum sheet was used as auxiliary electrode and Ag / AgCl as reference electrode;
[0059] ②Use constant current-time method to test material performance, and keep the current density at 50mA / cm 2 , record the working curve Figure 4 c. During the stability test, samples were injected into the gas chromatograph at regular intervals to detect gas products.
[0060] according to Figure 4 As shown in c, it shows that the Bi2S3 / Bi2O2CO3 nanosheet catalyst of the present invention has excellent stability in electrocatalytic carbon dioxide reduction to produce formic acid.
[0061] Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. Bi2S3 / Bi2O2CO3 nanosheet catalyst, characterized in that: The Bi2S3 / Bi2O2CO3 nanosheets are represented by the (011) and (013) crystal planes of Bi2O2CO3 and the amorphous phase of Bi2S3, and the Bi2S3 / Bi2O2CO3 interfaces are randomly distributed in the nanosheets.
2. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 1, characterized in that: Bi2O2CO3 nanoflowers are generated by a hydrothermal method, and then added into an aqueous solution containing thioacetamide and stirred to react to generate Bi2S3 / Bi2O2CO3 nanosheet catalysts.
3. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 2, characterized in that: The following steps are involved: 1) adding the raw material bismuth nitrate pentahydrate to a nitric acid solution containing citric acid monohydrate, stirring the solution evenly, adjusting the pH of the solution, transferring the solution to a hydrothermal kettle for hydrothermal reaction, taking out, centrifuging, washing, and drying to obtain Bi2O2CO3 nanoflowers; 2) Add Bi2O2CO3 nanoflowers into an aqueous solution containing thioacetamide and stir to obtain Bi2S3 / Bi2O2CO3 nanosheet catalyst.
4. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 1), the pH of the solution is adjusted to 7-9 using an aqueous solution of potassium hydroxide.
5. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 1), the hydrothermal reaction temperature is 160-200° C. and the reaction time is 16-28 h.
6. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 1), the washing is carried out in sequence with ultrapure water and ethanol.
7. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 2), the molar ratio of Bi2O2CO3 nanoflowers to thioacetamide is (1-3):
1.
8. The method for preparing the Bi2S3 / Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 2), the stirring temperature is 20-30° C. and the stirring time is 1-3 h.
9. Use of the Bi2S3 / Bi2O2CO3 nanosheet catalyst as claimed in claim 1 in the electrocatalytic production of formic acid from carbon dioxide.